Thorax Space Fluid Aspiration During Pleural Effusion in A Cat - Wudhia Windy Toliu; Muhammad Zulfadillah Sinusi; A. Rifqatul Ummah; Wa Ode Santa Monica (Journal of Basic Medical Veterinary, 2025)
Pleural effusion is the abnormal accumulation of fluid in the pleural cavity, which may result from infection, trauma, neoplasia or systemic disease. This condition often leads to acute respiratory distress in cats and requires immediate intervention. Thoracocentesis is the primary diagnostic and therapeutic method to evaluate the type of fluid and identify possible causative pathogens. This report to describe the management of pleural effusion in a four-year-old female Persian cat who presented with complaints of dyspnea, weakness, and decreased appetite. Physical examination and thoracic radiographs revealed fluid accumulation in the pleural cavity. Thoracocentesis was performed at the 7th or 8th intercostal space after the area was shaved and sterilized. The cat was placed in lateral recumbency and anesthetized before fluid aspiration with a syringe. Hematological examination revealed anemia, while radiographs showed radiopaque areas on the thorax. The aspirated fluid was clear pale yellow in color. Bacterial culture on NA medium revealed microbial growth, indicating infection as one of the causes of the effusion. In conclusion, thoracocentesis plays an important role in the diagnosis and therapy of pleural effusion, and helps speed up the patient's recovery. The cat recovered and was discharged after six days of intensive care.